PERAN BRIEF CBT TERHADAP TINGKAT DEPRESI DAN MASALAH BODY IMAGE PASIEN KANKER PAYUDARA DEWASA MUDA - Prischa Nova; Elmira N. Sumintardja (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2016)
Cancer is disease due to uncontrolled cell, until now it has not been found the cause of cancer. Treatment to breast cancer patients have an impact on physical, psychological, dan social. Treatment to breast cancer will give the impact on physical such as loss of hair and scars. By changes physically, perception of a person about his body relating to the psychological state of breast cancer patients (body image). Not only physically, the treatment of cancer will affect the psychological state of breast cancer patients. One psychological response to a chronic disease is depression. Individual with depression tends to develop negative thoughts, and individual with depression also tends to been distorted body image. To address the problem, then required psychological therapy. The brief CBT (Cognitive Behaviour Therapy) help breast cancer patients to resolve negative emotion by changing behavior and negative thought. The purpose of this research is to see the role of brief CBT on depression level and body image problem in young adulthood breast cancer patients. The design of this study was quasi-experimental study involving 5 subjects through convenience sampling. Data obtained by using interviews, observations, and quessionaire. The quistionnaire used was the beck Depression Inventory II (BDI-II) and Body Image Scale. Brief CBT is given 6 sessions within 60-90 menit each session. Data were analyzied using Wilcoxon Sign Rank Test. Five women completed the intervention, the analysis showed that after the end of treatment the score of depression show lower levels (p = 0,05) and Brief CBT marginally significant on body image (0,06).